Student Fellowship and Discipleship: An Effective Strategy for Enhancing the Learning Interest of Christian Students - Keluanan, Yane Henderina; Gusmanto, Yesi (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2024)
Student fellowship and discipleship play a significant role in increasing Christian students' learning interest. This study aims to explore the effectiveness of student fellowship and discipleship strategies in building learning motivation through spiritual and academic approaches. The research employs a descriptive qualitative method using in-depth interviews, observations, and document studies within Christian student groups in schools and church communities. The findings reveal that student fellowship creates a collaborative learning environment, while discipleship provides personal mentoring to strengthen students' character and sense of responsibility. Group discussions, communal prayers, and structured mentoring have proven effective in enhancing both learning interest and spiritual maturity among students. The discussion emphasizes the integration of faith-based values into the learning process as a holistic and effective approach. In conclusion, student fellowship and discipleship are relevant strategies for shaping Christian students with high learning motivation and strong character.